Recent progress on underwater soft robots: adhesion, grabbing, actuating, and sensing - Zhang, Yeming; Kong, Demin; Shi, Yan; Cai, Maolin; Yu, Qihui; Li, Shuping; Wang, Kai; Liu, Chuangchuang (Frontiers in Bioengineering and Biotechnology, 2023)
The research on biomimetic robots, especially soft robots with flexible materials as the main structure, is constantly being explored. It integrates multi-disciplinary contents such as bionics, material science, mechatronics engineering and control theory, and belongs to the cross-disciplinary field related to mechanical bionics and biological manufacturing. With the continuous development of various related disciplines, this field has become a hot research field. Especially based on the development of practical technologies such as 3D printing technology, shape memory alloy, piezoelectric materials and hydrogels at the present stage, the functions and forms of soft robots are constantly being further developed, and a variety of new soft robots keep emerging. Combined with its own material or structural characteristics with large deformation, soft robots have almost unlimited degrees of freedom compared with rigid robots, which also provides a more reliable structural basis for soft robots to adapt to the natural environment. Therefore, soft robots will have very strong adaptability in some special conditions. As a sort of robot made of flexible materials, soft robot's changeable pose structure is especially suitable for the large application environment of ocean. Soft robots working underwater can better mimic the movement characteristics of Marine life, in the hope of achieving more complex underwater tasks. The main content of this paper is to classify different types of underwater organisms according to their common motion modes, focusing on the achievements of some bionic mechanisms in different functional fields that have imitated various motion modes underwater in recent years(for example, the under water sucking glove[17],the underwater Gripper[49]and the self powered soft robot[68] etc.). The development of various task types(such as grasping function, adhesive function, driving or swimming function and sensing function, etc.) and mechanism realization forms of the underwater soft robot is described based on this category.